2019
DOI: 10.1039/c8dt05001e
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Mn(i)-complex catalyzed transfer hydrogenation of ketones and imines

Abstract: A series of Mn(i) complexes bearing amine and benzimidazole fragment containing ligands were investigated in the TH of ketones and imines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…[19] Several Mn complexes have been recently reported in the literature as very promising hydrogenation catalysts through TH processes. [20][21][22][23] However, the use of Mn-NHC in TH was only reported in 2019 when Pidko and co-workers demonstrated the remarkable efficiency of 17 in the reduction of ketones. [24] Complex 17 was capable to reduce a wide variety of aromatic and aliphatic ketones, using isopropanol as a hydrogen source in the presence of a low catalyst loading (75 ppm, 0.0075 mol%) and a strong base (KOtBu, 2 equiv.…”
Section: Transfer Hydrogenationmentioning
confidence: 99%
“…[19] Several Mn complexes have been recently reported in the literature as very promising hydrogenation catalysts through TH processes. [20][21][22][23] However, the use of Mn-NHC in TH was only reported in 2019 when Pidko and co-workers demonstrated the remarkable efficiency of 17 in the reduction of ketones. [24] Complex 17 was capable to reduce a wide variety of aromatic and aliphatic ketones, using isopropanol as a hydrogen source in the presence of a low catalyst loading (75 ppm, 0.0075 mol%) and a strong base (KOtBu, 2 equiv.…”
Section: Transfer Hydrogenationmentioning
confidence: 99%
“…The ligand's system was even simplified further as catalyst generated in situ from Mn(CO)5Br and ethylenediamine proved to efficiently promote TH of ketones with the same catalyst charge [17]. These promising results paved the way to further investigations performed by the groups of Leitner, [18] Kundu, [19] Khusnutdinova, [20] Pidko [21] and Chen [22]. They contributed to the field by expanding the library of catalytic systems for the reduction of ketones and aldehydes.…”
Section: Reduction Of Ketones Aldehydes Imines Nitroarenes and N-heterocyclesmentioning
confidence: 99%
“…A further step has been taken in the field when the groups of Kundu, [19] Khusnutdinova [20] and Sortais [25] demonstrated that their catalytic systems were also able to reduce imines, which are more reluctant substrates towards TH. The catalyst developed by Khusnutdinova was particularly active for the reduction of aldimines, the corresponding amines were produced in good to excellent yields up to 96% in the presence of 0.5 mol% of catalyst at 80 °C.…”
Section: Reduction Of Ketones Aldehydes Imines Nitroarenes and N-heterocyclesmentioning
confidence: 99%
“…Following the work of Beller in 2016, the groups of Sortais, [120] Leitner, [121] and Kundu [122] added to this transfer hydrogenation work with similar bidentate nitrogen-based Mn(I) catalysts (Scheme 19). Later, Chen used a biomimetic inspired bidentate catalyst (53) [123] similar to the catalyst from the Khusnutdinova group ( 46) for hydrogenation of carbon dioxide (vide supra).…”
Section: Development Of Manganese-catalyzed Transfer Hydrogenation Reactionsmentioning
confidence: 99%